Considering African art today: the case of the installation “La bouche du roi” (DAPesquisa, 2019)
This paper seeks to consider some specific aspects of contemporary art, specifically contemporary African art, through an examination of the installation "La bouche du roi" by Romuald Hazoumé of the Republic of Benin. It presents a qualitative analysis of this significant work of art and its aesthetic and critical particularities, through the use of bibliographic references that dialogue with the area of art. The results of this paper show that artwork today is not restricted to more developed countries, but also includes developing countries, thus revealing unique aesthetic-socio-cultural facets of, and thus enriching thoughts about, contemporary art today.
Keywords: Contemporary arts; African arts; Visual arts; “La bouche du roi”.